Vitamin D Deficiency in Adult Patients with Schizophreniform and Autism Spectrum Syndromes: A One-Year Cohort Study at a German Tertiary Care Hospital - Endres, Dominique; Dersch, Rick; Stich, Oliver; Buchwald, Armin; Perlov, Evgeniy; Feige, Bernd; Maier, Simon; Riedel, Andreas; van Elst, Ludger Tebartz (Frontiers in Psychiatry, 2016)
Introduction: Vitamin D has many immunomodulatory, anti-inflammatory, and neuroprotective functions, and previous studies have demonstrated an association between vitamin D deficiency and neuropsychiatric disease. The aim of our study was to analyze the prevalence of vitamin D deficiency in a one-year cohort of adult inpatients with schizophreniform and autism-spectrum syndromes in a naturalistic in-patient setting in Germany. Participants and methods: Our study was comprised of 60 adult schizophreniform and 23 adult high-functioning autism spectrum patients who were hospitalized Page: 2 between January and December of 2015. We compared our findings with a historical German reference cohort of 3,917 adults using Pearson’s two-sided chi-squared test. The laboratory measurements of 25-hydroxyvitamin D2/3 (25(OH)vitamin D) were obtained using a chemiluminescence immunoassay. Results: In the schizophreniform group, we found decreased (< 20 ng/ml) 25(OH)vitamin D levels in 48/60 (80.0%) of the patients. In the autism spectrum group, decreased levels were detected in 18/23 (78.3%) of the patients. 25(OH)vitamin D deficiencies were found in 57.3% of the historical control group. Particularly severe deficiencies (< 10 ng/ml) occurred much more frequently in the schizophreniform (38.3%) and autism spectrum groups (52.2%), when compared to the control group (16.3%). The recommended 25(OH)vitamin D values of > 30 ng/ml were observed in only 5% of the schizophreniform patients, 8.7% of the autism spectrum patients, and 21.9% of the healthy controls. Discussion: We found very high rates of 25(OH)vitamin D deficiency in both patient groups, and have discussed whether our findings might be related to alterations in the immunological mechanisms. Irrespective of the possible pathophysiological links between vitamin D deficiency and schizophrenia or autism spectrum disorders, a more frequent measurement of vitamin D levels seems to be justified in these patient groups. Further prospective, controlled, blinded, and randomized research should be conducted to analyze the effectiveness of vitamin D supplementation on the improvement of psychiatric symptoms.